Studies on cultural and morphological variability of Fusarium spp. and Rhizoctonia solani causing wilt and root rot complex of chickpea - Padamini, Rajkumari; Mathur, Kusum; Bhumita, Pukhram (Indian Journal of Plant Protection, 2020)
Fusarium oxysporum f.sp. ciceri (one isolate), Fusarium solani (five isolates) and Rhizoctonia solani (sixÂ isolates) were isolated and their pathogenicity were confirmed by growing chickpea in pathogen inoculatedÂ soil. The isolates of F. solani and R. solani exhibited considerable variations in growth, colony character,Â spore and sclerotial size. The five isolates of F. solani showed variations in radial growth and in sporeÂ morphology. The size of macro conidia ranged from 8.8 Ã— 2.5 Âµm of isolate UDP Rs-1 to 10.5 Ã— 2.7 Âµm ofÂ SRH Rs- 5 and micro conidial size ranged from 3.2Ã— 1.2 Âµm to 5.1Ã— 1.0 Âµm This showed that variabilityÂ in Fusarium spp. exists only with respect to cultural characters. Chlamydospores of Fusarium oxysporumÂ f.sp. ciceri measured 4.3-6.6 Âµm in size. The five isolates of F. solani did not show much variation inÂ chlamydospores size, and these ranged from 4.7-6.5 Âµm to 5.6-7.2 Âµm. All the six isolates of R. solaniÂ differed in colony characters and showed black colored cultures with 90.0 mm colony diameter on 7th dayÂ of incubation under uniform environments and medium. Sclerotial formation was recorded in all the sixÂ isolates of R. solani. Morphology of sclerotia varied from 1.0 Ã— 0.8 mm of UDP Rs-1 and 1.8 Ã— 1.3 mmÂ of TIB Rs-3. The results showed variations in growth and sclerotial formation among R. solani isolates.Â In vitro studies were conducted to determine the optimum range of temperatures for mycelial growth andÂ sporulation of the isolates of F. solani, Fusarium oxysporum f.sp. ciceri and R. solani. The results obtainedÂ in the present study indicates that out of the five temperatures viz., 15, 20, 25, 30 and 35â°C, the maximumÂ mycelial growth and sporulation of the isolate of Fusarium oxysporum f.sp. ciceri were recorded at 30â°CÂ and the minimum at 15â°C temperature. Also, all the five isolates of F. solani showed the maximum mycelialÂ growth and sporulation at 30â°C and the minimum growth and sporulation were recorded at 15â°C, the sixÂ isolates of R. solani showed the maximum mycelial growth at 30â°C and the highest sclerotial formationÂ at 35â°C and the minimum at 15â°C temperature. Fungi can grow over a wide range of pH but optimum forÂ mycelial growth may differ for each species or even within species. The relationship of pH to the mycelialÂ growth and sporulation of Fusarium spp. and sclerotial formation of R. solani was determined in vitro atÂ different pH levels viz., 4.0 to 8.0 at 20â°C. The present studies revealed that Fusarium spp. and R. solani grewÂ at wide range of pH (6-8). The maximum growth and sporulation of the isolate of Fusarium oxysporum f.sp.Â ciceri was observed at pH 7 while the minimum at pH 4. The five isolates of F. solani showed the maximumÂ growth and sporulation at pH 7 and the minimum at pH 4. The isolates of R. solani showed the maximumÂ growth and sclerotial formation at pH 7 and the minimum at pH 4.